Books for children, books for adults : age and the novel from Defoe to James - Michals, Teresa, 1963- (Cambridge, United Kingdom ; New York : Cambridge University Press, 2014)
"In this groundbreaking and wide-ranging study, Teresa Michals explores why some books originally written for a mixed-age audience, such as Daniel Defoe's Robinson Crusoe, eventually became children's literature, while others, such as Samuel Richardson's Pamela, became adult novels. Michals considers how historically specific ideas about age shaped not only the readership of novels, but also the ways that characters are represented within them. Arguing that age is first understood through social status, and later through the ideal of psychological development, the book examines the new determination of authors at the end of the nineteenth century, such as Henry James, to write for an audience of adults only. In these novels and in their reception, a world of masters and servants became a world of adults and children"--
1. Introduction -- 2. Rewriting Robinson Crusoe: age and the island -- 3. Dating Pamela: Mr. B., Goody Two-Shoes, and the age of consent -- 4. Rational moralists, highland barbarians, and the taste for adventures -- 5. Educating Dickens: Old Boys, Little Mothers, and school time -- 6. 'The time of real amusement': Henry James and the cult of adulthood.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: English fiction -- 18th century -- History and criticism; English fiction -- 19th century -- History and criticism; American fiction -- 18th century -- History and criticism; American fiction -- 19th century -- History and criticism; Books and reading -- Great Britain -- History; Books and reading -- United States -- History; Fiction -- Appreciation -- History; Children's literature -- History and criticism; Adulthood in literature; Children in literature; Roman anglais -- 18e siècle -- Histoire et critique; Roman anglais -- 19e siècle -- Histoire et critique; Roman américain -- 18e siècle -- Histoire et critique; Roman américain -- 19e siècle -- Histoire et critique; Livres et lecture -- Grande-Bretagne -- Histoire; Roman -- Appréciation -- Histoire; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Adulthood in literature; American fiction; Books and reading; Children in literature; Children's literature; English fiction; Fiction -- Appreciation; Great Britain; United States; Alter; Englisch; Kinderliteratur; Leser; Literatur; Engelska romaner -- historia; Amerikanska romaner -- historia; Böcker och läsning -- historia; Skönlitteratur för mellanåldern -- historia; Romaner -- mottagande -- historia; Barn i litteraturen; 1700-1899; dissertations; Criticism, interpretation, etc; History; Academic theses; Thèses et écrits académiques.